Níveis de isoleucina digestível sobre o desempenho de fêmeas suínas dos 15 aos 30 kg - Castilha, Leandro Dalcin (2011)
Aiming to determine the digestible isoleucine requirement for female swines from 15 to 30 kg, two experiments were conducted, a performance one and a nitrogen balance. In the first experiment, 40 crossbreed female swines of high genetic potential and average performance were used, with 15.00 ± 0.52 kg initial weight, distributed in a randomized blocks design, consisting of five treatments (0.45, 0.52, 0.59, 0.66, 0.73% digestible isoleucine), four replicates and two animals. At the beginning and the end of the performance experiment one animal per experimental unit was bleed for determination of plasma urea. At the end of the experiment, the second animal of each experimental unit was slaughtered to determine carcass composition and organ weights. In the second experiment, 20 castrated crossbred pigs were used, averaging 22.26 ± 1.79 kg of initial weight, distributed individually in metabolism cages in a randomized blocks design, consisting of five treatments (0.45, 0.52, 0.59, 0.66, 0.73% digestible isoleucine) and four replications. In the first experiment, there was quadratic effect (P<0,05) of digestible isoleucine levels over the daily feed intake, with estimation of best feed intake at level 0,704%. There was quadratic effect (P<0,05) of digestible isoleucine levels over efficiency of isoleucine utilization for weight gain, with increase until 0.506% of digestible isoleucine. In the second experiment, only N intake (g/kg BW0,75/day) was influenced (P<0,05) by digestible isoleucine levels, with linear increase on N intake values as digestible isoleucine levels were increased in the rations. The level of 0.506% digestible isoleucine, for female swines from 15 to 30 kg, provided the best efficiency of isoleucine utilization for weight gain, which digestible isoleucine:lysine relation was 0,51. The daily requirement of digestible isoleucine was 4,94 g/day, providing 1,56g of digestible isoleucine/Mcal of metabolizable energy